Influencing Factors on Rice Sheath Blight Epidemics in Integrated Rice-Duck System - Pin SU; Xiao-lan LIAO; Ya ZHANG; Huang HUANG (Journal of Integrative Agriculture, 2012)
Sheath blight, a disease caused by the fungus Rhizoctonia solani Kuhn (anamorph), has been the most economically significant disease of rice. It was frequently reported that the disease was well-controlled in integrated rice-duck system without the employment of fungicides. However, the effecting factors behind this phenomenon were rarely reported. In this research, experiment was carried out between two treatments, rice combined with ducks (RD) and conventional rice field without ducks rearing (CK) in early season rice paddy, to investigate the variations of sclerotia in floodwater and on rice plant, microclimate 10 cm above the waterline in rice paddy and activity of protective enzymes in rice plants. The results showed that the floating sclerotia in floodwater in RD was 86-91% lower than that in CK, and adhering sclerotia in rice plant in RD was 67-78% lower than that in CK. The relative humidity tested significantly lower and light intensity tested significantly higher in RD. The temperature in the early rice growth stages in RD was slightly lower than that in CK, but it was significantly higher (32.3–36.5°C) in the middle stage rice growth stages. The polyphenoloxidase (PPO) activity in RD were lower than that in CK, but the enhanced activity of phenylalanine ammonia-lyase (PAL), peroxidase (POD) and Chitinase was observed in different stages of rice growth in RD, especially the Chitinase which showed higher activity in all investigating days.